Alternative method of allelic discrimination - Rajeswari Avula; Dennis O'Kane; John L. Black (BioTechniques, 2014)
5′ nuclease assays for allelic discrimination use both a wild-type and a mutant probe. Here we present a new method for genotyping by 5′ nuclease assays that dispenses with the mutant probe, using the wild-type probe together with a probe for a reference gene known to be present in two copies to determine the copy number of the wild type allele relative to the reference gene. The copy number of the wild-type allele then determines the genotype: two copies indicates homozygous wild-type; one copy indicates heterozygous; and zero copies indicates homozygous mutant. We were able to use our method to correctly genotype three alleles of the thiopurine methyl transferase (TPMT) gene: TPMT *2 (c.G238C), *3B (c.G460A) and *3C (c.A719G). Our approach can be used as an alternate allelic discrimination strategy that is cost effective when multiple TaqMan assays are performed on a sample.